(3eONd Edi EOGQI GdCYeGd GdOhdjIs - (3CMeO(B, (3CMeO YHO GdQMeGfs ((3GdQjGVs (3OGQ GdeQjNs, 2001)
(3ebOeI hNdajI GbJUGOjI(B-(3HjFI EOGQI GdCYeGd GdOhdjI(B-(3JfXje hhXGFa GdCYeGd GdOhdjIs
Keywords: (3EOGQI GdCYeGds; (3GdTQcGJ GdOhdjIs